2023
DOI: 10.1002/lpor.202300025
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Thermo‐Optic Mach–Zehnder Interferometer on LNOI for Polarization Handling and Multiplexing

Abstract: Thin‐film lithium niobate (LN) on insulator (LNOI) is emerging as a promising integrated photonic platform. Thermo‐optic (TO) Mach–Zehnder interferometers (MZIs) on LNOI are demonstrated to be a viable and often preferred alternative to their electro‐optic counterparts for low‐speed and static applications, where stability and repeatability are crucial. Harnessing the unique and strong anisotropic TO effect of LN, a novel and versatile anisotropic TO MZI on x‐cut LNOI for polarization handling and multiplexing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In conclusion, we have demonstrated a 2 × 2 MZI monolithically integrated on the LNOI platform. The device uses TOPS to introduce phase shifts which feature a low P π = 44.4 mW achieved with CMOS compatible voltages below 5 V. The power consumption is among the lowest ever reported in comparable structures [35,36], and can be boosted using thermal isolation trenches [37]. We showed that the thermo-optically tuned MZI can reach extinction ratios above 31 dB symmetrically on both ports and reached optical response times as low as 0.7 µs by employing an overdrive protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have demonstrated a 2 × 2 MZI monolithically integrated on the LNOI platform. The device uses TOPS to introduce phase shifts which feature a low P π = 44.4 mW achieved with CMOS compatible voltages below 5 V. The power consumption is among the lowest ever reported in comparable structures [35,36], and can be boosted using thermal isolation trenches [37]. We showed that the thermo-optically tuned MZI can reach extinction ratios above 31 dB symmetrically on both ports and reached optical response times as low as 0.7 µs by employing an overdrive protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, LNOI is composed of a single-crystal LN film bounded to a SiO 2 interlayer with a bulk LN or Si substrate used as the carrier wafer . The excellent electro-optic, acousto-optic, ferroelectric, and nonlinear optical properties of LNOI retained from the LN crystal, in company with its high refractive index contrast (∼0.7) and extremely compact structure, make it promising in the area of integrated photonic devices and in biophotonics applications including SERS detection. Furthermore, the intrinsic roughness and defects formed during the fabrication process of LNOI provide additional defect levels and therefore make it more suitable for PIERS than LN bulk crystals. , However, the origin of LNOI-based PIERS is far from being thoroughly demonstrated.…”
mentioning
confidence: 99%